2021
DOI: 10.5194/essd-2021-262
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Emissions of greenhouse gases from energy use in agriculture, forestry and fisheries: 1970–2019

Abstract: Abstract. Fossil-fuel based energy use in agriculture leads to CO2 and non-CO2 emissions. We focus on emissions generated within the farm gate for crop and livestock production and from fisheries, providing information relative to the period 1970–2019 for both energy use and the associated greenhouse gas (GHG) emissions. Country-level information is generated from UNSD and IEA data on energy in agriculture, forestry and fishing, relative to use of: gas/diesel oil, motor gasoline, liquefied petroleum gas (LPG),… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 1 publication
0
5
0
Order By: Relevance
“…The initial capital costs of biogas‐powered refrigeration were found to be relatively high in a case study in Kenya involving biogas made from dairy cattle waste (Flammini et al, 2018), but the overall financial and economic returns were good. In addition, the research reported beneficial effects on soil quality, indoor air pollution, fertilizer use and efficiency, food loss, GHG emissions, and access to energy.…”
Section: Resultsmentioning
confidence: 99%
“…The initial capital costs of biogas‐powered refrigeration were found to be relatively high in a case study in Kenya involving biogas made from dairy cattle waste (Flammini et al, 2018), but the overall financial and economic returns were good. In addition, the research reported beneficial effects on soil quality, indoor air pollution, fertilizer use and efficiency, food loss, GHG emissions, and access to energy.…”
Section: Resultsmentioning
confidence: 99%
“…The GHG emission data presented herein cover the period 1990-2019 at the country level. They are available as open data, with DOI https://doi.org/10.5281/zenodo.7310932 (Flammini et al, 2022).…”
Section: Data Availabilitymentioning
confidence: 99%
“…Discussion started: 28 November 2022 c Author(s) 2022. CC BY 4.0 License.Uncertainties in GHG Emissions from Fuel Combustion, Table3;Flammini et al, 2022). Uncertainty in activity data was then combined with uncertainty in fuel emission factors (−15 % to 18 %), computed by taking the IPCC lower and upper values of emissions factors of wood/wood waste.…”
mentioning
confidence: 99%
“…It is difficult to argue for these cost reductions unless society, rather than the enterprises, realizes the benefits and compensates the cost difference between a smoke-free and a conventional polluting biochar-producing technology. The co-benefits of a clean energy technology such as the PPV300 usually significantly outweigh the financial benefits [30,31]. Another alternative, from the society perspective, is of course to use regulations as incentives favoring "green" technologies to reduce the externalities, which rather force the enterprise to strive for such cost reductions (Flammini et al, 2018) [30].…”
Section: The Ppv300 Vs Cheaper Alternatives For Biochar Productionmentioning
confidence: 99%
“…The co-benefits of a clean energy technology such as the PPV300 usually significantly outweigh the financial benefits [30,31]. Another alternative, from the society perspective, is of course to use regulations as incentives favoring "green" technologies to reduce the externalities, which rather force the enterprise to strive for such cost reductions (Flammini et al, 2018) [30]. Although such incentives would not mitigate the original hindrances, they would further support the expansion of coffee husk-biochar production in Vietnam.…”
Section: The Ppv300 Vs Cheaper Alternatives For Biochar Productionmentioning
confidence: 99%